Analiza časa pri Wittgensteinu in Merleau-Pontyju - Toplak, Aljoša (Analiza (Ljubljana), 2025)
I will argue that Wittgenstein distinguishes three senses in which we speak of seeing the content of our perception. These senses are: seeing in the literal sense, as colors and shapes; seeing in some consciously established regard, such as recognizing a rabbit in the duck-rabbit illusion; and seeing an aspect in some spontaneous regard. I will compare this starting point with the idea of the conceptual horizon, through which Merleau-Ponty interprets time as an existential situation. I will show the surprising similarities in the thought of these two philosophers, especially when they meet in the reflections in Remarks on the Philosophy of Psychology, where Wittgenstein imagines a hypothetical person who is “aspect- blind,” and the interpretation of the anomalous behavior of a patient suffering from brain damage, which we find in Merleau- Ponty’s Phenomenology of Perception. I will then situate Merleau- Ponty within the discourse surrounding three models of temporal consciousness, which I roughly divide into retentional, extensional, and kinematic models. I conclude the contribution with Wittgenstein’s distinction between time as a phenomenal and a public coordinate system. Through this, we will develop some fruitful images for thinking about the concept of time.
Keywords: Fenomenologija; fenomenologija časa; filozofija duha; filozofija jezika; phenomenology of mind; philosophy of language; philosophy of time